Estimation of age at onset of linear enamel hypoplasia. New calculation tool, description and comparison of current methods - Dabrowski, Pawel; Kulus, Michal Jerzy; Furmanek, Miroslaw; Paulsen, Friedrich; Grzelak, Joanna; Domagala, Zygmunt (Journal of Anatomy, 2021)
Enamel Hypoplasia (EH) is known to be a useful indicator for wide range of detrimental factors in early childhood in past populations, such as nutritional disturbances, mechanical trauma, disease, metabolic, and/or genetic disorders. EH may be divided into three categories: pits, grooves, and lines, where the last two are referred to as “Linear Enamel Hypoplasia” (LEH). The regularity of enamel formation allows retrospective determination of the age of LEH formation. The current article reviews and compares the best-known methods used to estimate age at LEH formation and provides a new computational tool. Growth curves for canines and incisors were developed based on tooth growth tables by previous authors. Optimal models were selected using the Akaike Information Criterion. A Microsoft Excel spreadsheet was created to calculate age at LEH formation using the most common methods. All method results were compared with an archaeological sample (44 teeth of 18 individuals from an early modern cemetery from Wrocław, Poland) and a theoretical model. The results of the methods were compared pairwise with Bland-Altman plots. The current article provides a quick and easy-to-use tool for analyzing LEH chronology and comparing the results of different methods. As shown by the Bland-Altman plots, most methods provide approximately consistent results for LEHs formed at around 2–3 years of age. However, LEHs formed particularly early or late are more prone to discrepancies between different methods. Comparison of the age at LEH formation obtained by different methods should be done carefully - and the new LEH calculation tool with optimized equations provided in this publication can facilitate this process.
CRIS-Team Scopus Importer:2021-06-11
Keywords: enamel hypoplasia; mathematical modeling; physiological stress